Working capital management impact on profitability : empirical study based on Portuguese firms - Serrasqueiro, João Nogueira (2016)
The main objective of this dissertation is to understand the impact of working capital management on profitability. This study comes in a period where managers are trying to push up the businesses activities and management policies are changing, aiming to adapt to the new economic context. The working capital management appears with relevance in several studies given the importance of the short-term policies in the value creation for the shareholders. In the literature are present several studies aiming to test the efficiency of working capital management and the relation with the profitability in the firms. The authors have been studying working capital by testing within the management policies, the size of the firm, the industry and geographical impact on the profitability. The core difference of this dissertation comparing with the previous studies is the role of working capital management and the impact in profitability of Portuguese firms, how firms in Portugal are managing working capital and what relevance does it bring to actual performance. In front of the recent economic difficulties and the struggling in credit finance experienced by Portuguese companies, the working capital management can be an important source of credit through an efficient management of the current assets and liabilities. The study will be developed under descriptive and empirical statistics and the data will be collected from Bloomberg for the period 2002-2006 in an annual basis. From the initial raw data will be excluded the data outliers and firms without complete information. In order to proceed correctly through the analysis, some control variables will be added and some tests will be carried out. The data will be treated and disposed in panel data to provide an intuitive analysis and interpretation to the reader. This dissertation will follow some papers and previous studies which tested similar hypothesis but in different countries with different economic-cultural aspects.